"It's just everywhere!" Children and parents discuss the marketing of sports wagering in Australia. (14th August 2016) - Pitt, Hannah; Thomas, Samantha L.; Bestman, Amy; Stoneham, Melissa; Daube, Mike
Abstract: Objective: To investigate how children and adults recall the content and promotional channels for sports wagering marketing. Methods: A mixed methods study of 152 parent/child (8–16 years) dyads was conducted at AFL (Australian Football League), NRL (National Rugby League), and soccer sporting sites in New South Wales and Victoria, Australia. Questions related to the frequency of viewing AFL and NRL matches, sports wagering promotions and perceptions of the normalisation of wagering in sport. Descriptive statistics and thematic analysis were used to analyse data. Results: Children recruited from NRL (n=75, 96.2%) and AFL (n=46, 92.0%) sites were significantly more likely to have recalled having ever seen a promotion for sports wagering as compared to children from Soccer sites (n=18, 75.0%) (p<0.05). Children and adults identified seeing sports wagering promotions in similar environments, most commonly on television, and at stadiums. Three‐quarters of children (75.0%) and the majority of adults (90.0%) perceived that sports wagering was becoming a normal part of sport. Conclusion and Implications: This research shows that children engaged in particular sports have high awareness of wagering marketing, particularly as seen on television or at sporting matches. Regulation should comprehensively address the placement, quantity and content of wagering marketing aligned with sport to prevent current and/or future gambling harm.